Tourism : principles, practices, philosophies - Goeldner, Charles R.; Ritchie, J.R. Brent (Hoboken, New Jersey : Wiley, 2012)
The 12 th Edition of Tourism: Principles, Practices, Philosophies explores major concepts in tourism, what makes tourism possible, and how tourism can become an important factor in the wealth of any nation. It is written in global terms, making it appropriate not only in the US but also for our subsidiary markets.
Chapter 1: Tourism in Perspective. -- Chapter 2: Tourism Through the Ages. -- Chapter 3: Career Opportunities. -- Chapter 4: World, National, Regional and Other Organizations. -- Chapter 5: Passenger Transportation. -- Chapter 6: Hospitality and Related Services. -- Chapter 7: Organizations in the Distribution Process. -- Chapter 8: Attractions, Recreation, and Other Tourist Draws. -- Chapter 9: Motivation for Pleasure Travel. -- Chapter 10: Cultural and International Tourism for Life's Enrichment. -- Chapter 11: Sociology of Tourism. -- Chapter 12: Tourism Components and Supply. -- Chapter 13: Measuring and Forecasting Demand. -- Chapter 14: Tourism's Economic Impact. -- Chapter 15: Tourism Policy: Structure, Content, and Process. -- Chapter 16: Tourism Planning, Development, and Social Considerations. -- Chapter 17: Tourism and the Environment. -- Chapter 18: Travel and Tourism Research. -- Chapter 19: Tourism Marketing. -- Chapter 20: Tourism's Future.
Includes bibliographical references and index.
Keywords: TOURISM